INDIKASI MANAJEMEN LABA PADA PERUSAHAAN YANG MELAKUKAN RIGHT ISSUE DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - Sandyaswari, Ni Putu; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The rights issue process in the company will publish the offering prospectus which contains interesting information for existing shareholders to purchase. In this condition, it is possible if the manager has information about the company more than the shareholders manager of engineering term profits (earnings management) to obtain 31 samples of this study was the observation of the rights issue the company and listed on the Indonesia Stock Exchange in 2003-2011. The hypothesis of this study was analyzed using independent sample T-test and simple linear regression. In addition, test results done with discretionary accruals that Modifikasian Jones model. Results of testing this hypothesis can not show that the company's earning management to increase profits (income maximization) before the rights issue; it shows that companies earning management by decreasing the profit (income minimation) before the rights issue and profit management affect the company's performance in the year after right issue.
Keywords: Earnings Management, Discretionary Accruals, Rights Issue, Company Performance